Desempenho de coroas unitárias anteriores cimentadas implanto-suportadas sobre abutments angulados em teste de compressão à fratura - Alderete, Alfredo (2011)
Single cement-retained implant-supported crowns in the anterior maxillary region are considered as restorations with a high rate of clínical success when the dental implant is placed correctly, been their behavior before bite forces supported in the literature. Implants placed in buccal or palatal angulation can cause drawbacks in the final aesthetic of the restoration, needing the use of angled abutments together with cemented crowns, in order to compensate the fixture’s position in these cases. The behavior of this type of restorative modality is not established in the literature. The objective of this in vitro study is to value the fracture resistance of implants units supporting cemented crowns in different degrees of the abutment angulation. Three test groups of abutments for cement-retained crown, with different angulations (0º - 17º - 35º), were formed. Each group was made of ten abutments installed in external hexed implant’s analogs of platform 4,1 mm (P-I Brånemark Philosophy, EXOPRO). 0º and 17º abutments were used without modifications, and the 35º abutment was made from customization of Co-Cr UCLA type abutment (P-I Brånemark Philosophy, EXOPRO). Standardized maxillary central incisor metal-ceramic crowns and metal copings without ceramic coverage, were fabricated and temporary cemented in number of five for each abutment angulation group. All specimens were tested for fracture resistance using compressive force applied on the palatal surfaces with a 45 degree angulation. Fracture resistance values, measured in Kilo-Newton (kN), were subjected to ANOVA Two-Way test of variance and Turkey test. The significance level considered in these tests was of 5% (p<0,05). The median fracture resistance for the abutments with the cement-retained metalceramic crows was: 0º 0,32 kN, 17º 0,37 kN, 35o 0,4 kN; and for the abutments with the cement-retained metal copings: 0º 0,96 kN, 17º 0,64 kN, 35º 0,74 kN. In all specimens fractured took place in the retention screw, without compromise of the metal-ceramic crows or the metal copings. The metal-ceramic crown group showed similar fracture resistance values in all abutment angulations, been this performance inferior comparing with the metal coping group in their entire abutment angulation groups. Confronting this results with the physiological bite force values of the maxillary incisor region, it can be concluded that the implant/screw joint of tested prosthetic abutment angulation, supporting metal ceramic crowns, have physical properties that allow their use in the mentioned region.